Triglyceride to High Density Lipoprotein Cholesterol Ratio in Acute Myocardial Infarction And Its Relationship with Angiographic Severity (Bangladesh Heart Journal, 2021)
Background: In acute myocardial infarction (AMI) the extent of the coronary artery lesion is evaluated by coronary angiogram (CAG). Recent evidences suggest that, ratio of triglyceride and high-density lipoprotein cholesterol (TG/HDL-C) could be a non-invasive marker for the prediction of the extent of coronary artery lesion. The aim of this study was to evaluate the association between TG/HDL-C ratio and the extent of coronary artery lesion assessed by coronary CAG among AMI patients. Objective: The aim of this study was to assess relationship between TG to HDL-C ratio and extent of coronary artery lesion in AMI patients.Materials & Method: This cross-sectional study was carried out in the Department of Cardiology, Chittagong Medical College Hospital in 224 admitted AMI patients. Blood samples were taken within 24 hours of admission following AMI for fasting lipid profile assessment, (total cholesterol (TC), HDL-C, low-density lipoprotein cholesterol (LDL-C) and TG). Each patient was underwent CAG within 2 to 6 weeks of the events and angiographic findings were classified according to presence of significant stenosis, number of vessel involved and Gensini score.Results: The subjects consisted of 197 males and 27 females with a mean age of 51.24 (±11.22) years. Mean value of TC was 185.74 (±41.96) mg/ dL, TG was 222.17 (±99.05) mg/dL, HDL-C was 38.92 (±5.46) mg/dL, LDL-C was 127.99 (±36.94) mg/dL, TG/HDL-C was 5.91 (±2.99), median Gensini score was 28 (Range:1-146). Analysis of receiver operating characteristic curves showed that only TG/HDLC and TG were useful for detecting high Gensini score (score >42), with the former more area under the curve (AUC: 0.611; 95% CI: 0.531-0.691; p=0.008). The TG/HDL-C was an independent predictive factor (Odds ratio: 2.706; 95% CI: 1.397-5.242; p = 0.003) for the presence of significant coronary artery lesion on CAG. Linear regression analysis revealed that, age and TG/HDL-C ratio significantly predicted Gensini score.Conclusion: TG and HDL-C ratio was independently associated with extent of coronary artery lesion.Bangladesh Heart Journal 2021; 36(2): 82-88